Kesejahteraan Psikologis Karyawan di Tempat Kerja: Systematic Literature Review - Putri Lara Sati; Umi Anugerah Izzati (MANABIS: Jurnal Manajemen dan Bisnis, 2025)
Abstract: This study aims to identify factors that influence employee psychological well-being through a systematic literature review approach. The purpose of this study is to systematically identify factors that influence employee psychological well-being based on the results of recent research. Data were obtained from 10 scientific articles published in 2021–2025 that were relevant and met the inclusion criteria. The results showed that psychological well-being was influenced by two groups of factors, namely individual factors and organizational factors. Individual factors include job satisfaction, positive psychological capital, burnout, job autonomy, job engagement, self-efficacy, and performance. Meanwhile, organizational factors include business performance, workplace bullying, and social support. These findings confirm that psychological well-being is the result of the interaction between personal characteristics and the work environment. Therefore, organizations need to create a work culture that supports and pays attention to the psychological aspects of their employees because it is important for an organization to pay attention to employee psychological well-being as part of a company performance improvement strategy so that the company's main goals and targets can be achieved properly.